Developing a Unified Service Model for Collaborative Modeling of Logistics Services - Augenstein, Christoph; Müller, Holger; Franczyk, Bogdan (Budowa zunifikowanego modelu usług dla kolaboracyjnego modelowania serwisów logistycznych, 2010)
Engineering and management of service systems and services is complex and involves the legwork of many different stakeholders. A structured approach may lead to significant better results in these tasks. Modeling becomes necessary to cope with the complexity of service systems and services. Due to the big variety of stakeholders and their interests, many models on the same services exist. In this paper we therefore present a method on how to develop a unified service model for the logistics domain which has the ability to integrate various stakeholder models and to keep them in a consistent manner, so that each model stays valid when put into model space.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 27-38
Keywords: service model; modeling; logistics